2021
DOI: 10.3389/frobt.2021.613574
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Knee Joint: Trends in the Hardware Systems Development

Abstract: The knee joint is a complex structure that plays a significant role in the human lower limb for locomotion activities in daily living. However, we are still not quite there yet where we can replicate the functions of the knee bones and the attached ligaments to a significant degree of success. This paper presents the current trend in the development of knee joints based on bio-inspiration concepts and modern bio-inspired knee joints in the research field of prostheses, power-assist suits and mobile robots. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…(2) The motion pattern originates from contact surfaces and ligament insertions, in which the joint kinematics can be customized by setting the condition of the four-bar mechanism in the mathematical model. Compared to a knee with circular contact surfaces [33][34][35][36] or cam-based surfaces [40,41], the theoretical modeling of the bioinspired knee allows a more convenient yet straightforward design method for required features, such as the slip ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The motion pattern originates from contact surfaces and ligament insertions, in which the joint kinematics can be customized by setting the condition of the four-bar mechanism in the mathematical model. Compared to a knee with circular contact surfaces [33][34][35][36] or cam-based surfaces [40,41], the theoretical modeling of the bioinspired knee allows a more convenient yet straightforward design method for required features, such as the slip ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The meshed gears act in the same way as the rolling contact surface, and not only achieve motion with changeable ICR via contact of the femur and tibia [37,38], but also realize the elastic characteristic of the bending knee [39]. The condylar structure of the bioinspired knee traces the profiles of the femur and tibia bones as well, along with the motion of ligaments [40]. The femur and tibial condyle were created by four-bar linkage and were designed for a cam mechanism [41].…”
Section: Introductionmentioning
confidence: 99%
“…The onset of secondary conditions like cartilage wear and KOA is a significant risk if these injuries are not promptly addressed. Treatment strategies vary based on the severity of the injury and include conservative approaches, meniscus suturing, and meniscectomy [76,77]. Research by Magyar et al [72] demonstrates that patients with meniscal injuries exhibit significantly reduced walking speed and knee range of motion (ROM) alongside increased cadence, step length, and duration of both support and double support phases.…”
Section: Figurementioning
confidence: 99%
“…We controlled the motor position and slightly rotate the knee joint from 0 to 120 • flexion and record the video to measure the center of rotation of the knee joint. The device's center of rotation is plotted and compared with human biomechanics of the knee joint (Etoundi et al, 2021), as shown in Figure 8B. The result shows the misalignment between the device's center of rotation and human biomechanics of the knee joint is 0.7, 2.2, 3.5, 4.3, and 3.4 mm when the knee joint rotates 20 • , 40 • , 60 • , 80 • , 100 • , 120 • , respectively.…”
Section: Joint Misalignment Measurementmentioning
confidence: 99%